2021
DOI: 10.4018/978-1-7998-8081-3.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Model to Highlight the Relation of Digital Trust With Privacy and Security for the Blockchain Technology

Abstract: Digitalization uses digital technology to change a business model and provide new revenue models and value-producing opportunities. Blockchain is a type of database that stores various kinds of information in blocks that form a chain of information. It is one of the secured ways of transferring and storage of data. Blockchain is helping in creating trust for digitalization among its users. This research aims to study the impact of trust in blockchain by analyzing the privacy and security concerns that can impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…, 2022). Trust is critical in convincing the electronics supply to incorporate such a business model (Mukherjee et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022). Trust is critical in convincing the electronics supply to incorporate such a business model (Mukherjee et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge and understanding are considerable roadblocks to the circular electronics industry. The consensual and overall benefits of the SC should be clarified and disseminated (Mukherjee et al, 2021). As a result, managers must take priority on interaction and collaboration.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Instead of being copied or transferred, digital assets are distributed and an immutable asset is created. The asset is decentralized and enables public transparency and full real-time access (Mukherjee et al. , 2021b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Instead of being copied or transferred, digital assets are distributed and an immutable asset is created. The asset is decentralized and enables public transparency and full real-time access (Mukherjee et al, 2021b). A transparent change ledger maintains the integrity of a document creating confidence in the asset (Kumar et al, 2022b;Sriyanto et al, 2022).…”
Section: Blockchain In Retail Supply Chainmentioning
confidence: 99%
“…The blockchain framework in the agriculture supply chain could be utilized for recognizability, water management, agro-food assembling, and data security (Mukherjee et al, 2021c). In a full review on the use of blockchain research in farming, the researchers demonstrated that blockchain acceptance is a naïve phase and organised current blockchain-based research under 4 measurements, including recognizability, engineering, data framework, and other random applications (Ghode et al, 2020).…”
Section: Literature Review 21 Blockchain In Agriculture Supply Chain ...mentioning
confidence: 99%